Mother’s Characteristics and Socioeconomic Status as Possible Risk Factors for Children’s Caries in Jordan - Omar Al-Rashdan; Zaid AlZoubi; Mahmoud Ibrahimi; Amal Al-khraisha; Nabeel Almajali (International Journal of Dentistry)
Background. Clinical oral health status of children affects their health-related quality of life. A major determinant of oral health is early childhood caries, which possesses a negative effect. Objective. The primary objective of the study was to examine the association between socioeconomic status and different mother’s characteristics and the risk of dental caries in children using the decay missing filled (DMF) score as an indicator. Methods. This was a cross-sectional descriptive study that was in the pediatric dental clinic in Hashem Ibn Al-Hussein medical military hospital in Jordan. Pearson correlation was used to examine associations between two continuous variables. Linear regression was used to detect variables that might predict the decayed missing filled teeth (dmft) score of the child. Results. A total of 264 children were enrolled in the study. Average age of children was 4.80 ± 1.99 years, and average mothers’ age was 32.74 ± 5.68. Mothers had an average DMFT score of 8.84 ± 5.39, while children had an average dmft score of 6.17 ± 4.82. There was no association between the mother’s age and the dmft score of the child (Pearson correlation = 0.08, and P value = 0.215). However, a moderate, statistically significant correlation was found between the mother’s and the child’s DMFT scores (Pearson correlation = 0.418, and P value = 0.001). Children who belonged to low and middle-income families had a higher dmft score compared to those that belonged to families with high income. Conclusion. Socioeconomic status of the family, mother’s habits, dental hygiene, and education level are important factors that influence the child’s oral health. Strategies that focus on children with these characteristics can help them achieve better oral health.